Free-Breathing, Non-Gated Heart-To-Brain CTA in Acute Ischemic Stroke: A Feasibility Study on Dual-Source CT - Liu, Jiabin; Wang, Chen; Li, Qing; Duan, Xianggong; Zhu, Xiaolian; Wang, Jiahong; Du, Xiangying; Lu, Jie; Li, Kuncheng (Frontiers in Neurology, 2022)
Purpose: To validate the feasibility of free breathing, non-gated high pitch heart to brain CTA in acute ischemic stroke and the capability of non-gated heart-brain CTA in showing cardiac anatomy. Materials and methods: The study protocol was approved by the institutional medical ethics review board. Free breathing, non-gated high pitch heart to brain CTA was performed on patients of acute ischemic stroke referred for multi-model CT using a third-generation dual source CT. Patients scheduled for ECG-triggered heart to brain CTA served as controls. Quantitative and/or qualitative image quality of the four cardiac chambers, left atrial appendage, interventricular and interatrial septa, carotid arteries and coronary arteries was evaluated and compared between the two groups. Results: Free breathing, non-gate high pitch heart to brain CTA was performed on 30 patients of acute ischemic stroke, while the control group included 31 cases. There is no significant difference in image quality of CTAs between the two groups at cardiac chambers and carotid arteries. The image quality of coronary arteries also showed no significant difference between the two groups. The mean dose length products of CTA in the two groups were 129.1±30.5 mGy*cm and 121.6±30.3 mGy*cm, respectively. Cardiac abnormality can be shown in acute ischemic stroke patients. Conclusion: It is feasible to use free breathing, non-gated high pitch heart to brain CTA with dual source CT in acute ischemic stroke for cardiac etiology screening.